Magistracy and Imperium: from the Monarchy to the Principate (Circe de clásicos y modernos, 2018)
We analyze the concepts and terms regarding potestas, vis an virtus, particularly those of imperium, its definition and the magistracy that supported it; regarding the dictator, we highlight the limitations and excesses in the exercise of imperium and its historical development; we noted the crisis of the magistracy, emphasizing the consulate at the end of the Republic. We examined the Cicero’s proposal for ending the crisis: the autocracy with a princeps; similarities and differences between the consul, the proconsul, the dictator, the dux and the princeps. It treats a key problem: vitium and virtus in politics and in the politics of the period.
Keywords: magistracy; potestas; imperium; vis; virtus